2020
DOI: 10.1097/njh.0000000000000704
|View full text |Cite
|
Sign up to set email alerts
|

An End-of-Life Care Educational Series to Improve Staff Knowledge and Comfort Levels

Abstract: Nursing staff play a key role in enhancing a patient's quality of life during end of life; however, they perceive lack of knowledge to be the largest barrier in providing quality end-of-life (EOL) care. Literature suggests that implementation of palliative and EOL care education can improve nursing EOL care practices. In order to address the gap in nursing knowledge and comfort, a quasi-experimental study was conducted; this study included the implementation of a multimodal EOL care educational series on an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…[11][12][13] One study found that training offered for 6 months via multiple delivery forms was successful in improving nursing knowledge of and comfort with end-of-life care. 10 Similarly, a study by Chrastek et al 12 found that a train-the-trainer End-of-Life Nursing Education Consortium (ELNEC) course improves knowledge of pediatric palliative care. Three studies also found that their education improved nursing practice through increased knowledge of pediatric palliative care practices (ie, symptom management) and intent to make practice changes.…”
Section: Adult Palliative Care Education Interventions For Nursesmentioning
confidence: 99%
See 2 more Smart Citations
“…[11][12][13] One study found that training offered for 6 months via multiple delivery forms was successful in improving nursing knowledge of and comfort with end-of-life care. 10 Similarly, a study by Chrastek et al 12 found that a train-the-trainer End-of-Life Nursing Education Consortium (ELNEC) course improves knowledge of pediatric palliative care. Three studies also found that their education improved nursing practice through increased knowledge of pediatric palliative care practices (ie, symptom management) and intent to make practice changes.…”
Section: Adult Palliative Care Education Interventions For Nursesmentioning
confidence: 99%
“…A variety of education delivery methods were used in the studies. One study used multiple methods of education delivery (ie, in-services, case studies, and interactive discussions) to educate pediatric hematology/oncology nurses on end-of-life and palliative care 10 . Three studies explored the impact of in-person and online pediatric palliative care courses on nursing practice, nursing knowledge, or practice change 11-13 .…”
Section: Pediatric Palliative Care Education Interventions For Nursesmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5][6][7][8] Literature shows that instruction on how to provide this type of care increases the skill and competence of clinicians who provide it. 8 In addition, after receiving pediatric palliative care training, health care staff perceive decreased levels of suffering in patients and their families at end of life. 9 Clinicians provide more culturally sensitive care when they assess and respect family values, beliefs, and traditions related to health and illness.…”
Section: Introductionmentioning
confidence: 99%
“…Research indicates that providing high-quality EOL care requires substantive staff training 3-8 . Literature shows that instruction on how to provide this type of care increases the skill and competence of clinicians who provide it 8 .…”
Section: Introductionmentioning
confidence: 99%